Answer: (x - 5, y - 6)
=====================================
Step-by-step explanation:
Let's say that point P is at (0,0). Using the original rule (x+5, y+6), we would add 5 to the x coordinate and 6 to the y coordinate to land at (5,6) which is point P '
Now the teacher wants you to start with point P ' and move back to point P. The rule to do this is basically the inverse or opposite of what the original rule states.
Instead of "add 5 to x", we "subtract 5 from x" to have x-5 as part of the rule. Similarly, undoing "add 6 to y" means we have "subtract 6 from y" to have y-6.
That's how (x-5, y-6) is the complete opposite or inverse of (x+5, y+6)
The first rule shifts P five units to the right and six units up to land on P'
The second rule moves P ' five units to the left and six units down.
If you apply either rule in any order, but do so together, then the point always goes back to its original starting location.